2019
DOI: 10.1590/1678-4162-10710
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de pelagens em equinos da raça Campolina

Abstract: RESUMO Desde tempos remotos, a pelagem é valorizada no agronegócio equestre. Em animais Campolina, objetivou-se avaliar a ocorrência de pelagens e a distribuição entre sexos nos estados do Brasil, assim como verificar a frequência desse fenótipo nos acasalamentos e associá-lo com medidas lineares e qualidade da marcha. Foram selecionados 44.437 registros definitivos e utilizaram-se testes de qui-quadrado para avaliar a distribuição de pelagens entre sexos, estados e décadas. Por análise descritiva, foi obtida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…About 23.8% (n=722) of the grullo horses had both parents registered as duns, which is the most frequent mating ( Table 1). Since dun is the prevalent coat color in Campolina horses [10], this agrees with practical knowledge indicating that grullo animals are frequently born from dun animals.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…About 23.8% (n=722) of the grullo horses had both parents registered as duns, which is the most frequent mating ( Table 1). Since dun is the prevalent coat color in Campolina horses [10], this agrees with practical knowledge indicating that grullo animals are frequently born from dun animals.…”
supporting
confidence: 88%
“…Hence, one of the parents of a grullo animal must carry the D allele (Table 1). Mendes et al observed similar inconsistencies for other coat colors too [10].…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…The growth of the Mangalarga herd that began in the 1960s reflected the general expansion of Brazilian horse breeding at that time. Costa et al (2005) and Baena et al (2020) observed an increase in the number of births of Mangalarga Marchador horses in the 1960s, similar to that of Mendes et al (2018) for the Campolina breed.…”
Section: Demographic Analysismentioning
confidence: 62%